2020
DOI: 10.3928/00220124-20191217-02
|View full text |Cite
|
Sign up to set email alerts
|

Continuing Education as a Core Component of Nursing Professional Development

Abstract: Nursing professional development and continuing nursing education are often used interchangeably. However, there is a difference, and as educators we need to be able to speak to these differences. This article depicts the unique aspects of both and their valuable contributions to the profession of nursing. [ J Contin Educ Nurs. 2020;51(1):6–8] .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
4
0
2
Order By: Relevance
“…Aos achados específicos relacionados ao controle e alívio da dor, encontrou-se que os profissionais têm percepção de que os bebês sentem dor, porém a mesma ainda é avaliada de forma subjetiva. Os participantes revelaram não ter conhecimento de que a simples manipulação já é suficiente para causar um estímulo álgico e que, principalmente, diante de procedimentos sabidamente dolorosos como a punção arterial, faz-se premente um planejamento adequado e prévio, voltado à prevenção e minimização dos efeitos negativos provocados pela dor 21 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Aos achados específicos relacionados ao controle e alívio da dor, encontrou-se que os profissionais têm percepção de que os bebês sentem dor, porém a mesma ainda é avaliada de forma subjetiva. Os participantes revelaram não ter conhecimento de que a simples manipulação já é suficiente para causar um estímulo álgico e que, principalmente, diante de procedimentos sabidamente dolorosos como a punção arterial, faz-se premente um planejamento adequado e prévio, voltado à prevenção e minimização dos efeitos negativos provocados pela dor 21 .…”
Section: Discussionunclassified
“…Utilizar somente o choro ou agitação do bebê como parâmetro de avaliação torna tal mensuração inadequada e incompleta. Ainda é necessário sensibilizar e capacitar a equipe quanto às formas de avaliação da dor no bebê, e a partir de sua adequada identificação possam ser implementadas medidas de alívio efetivas para sua prevenção ou minimização 21 .…”
Section: Discussionunclassified
“…Regarding the specific findings related to pain control and relief, it was found that the professionals perceive that the newborns feel pain, although it is still assessed subjectively. The participants revealed that they were not aware that simple handling is enough to cause a painful stimulus and that, mainly in the face of known painful procedures such as arterial puncture, adequate and prior planning becomes crucial, aimed at preventing and minimizing the negative effects caused by pain 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Using only the newborn's crying or agitation as evaluation parameters turns such measurement inadequate and incomplete. It is also necessary to sensitize and train the team on the ways of assessing pain in infants and, from its proper identification, effective relief measures may be implemented for its prevention or minimization 21 .…”
Section: Bundle and Neonatal Pain Reliefmentioning
confidence: 99%
“…This is an excellent example of continuing education. Continuing education may be delivered with a variety of programs, activities, and technologies (Shinners & Graebe, 2020) such as education courses to enhance teaching ability among clinical instructors. George et al (2020) also pointed out that nurse educators can use strategies such as use of caring, competent clinical instructors, self-reflection, peer-support, and debriefing to enhance students' clinical learning experiences.…”
Section: Literature Reviewmentioning
confidence: 99%